The Correlation Between Student's Engagement and Reading Comprehension While Using Quizlet Gamification for Vocabulary Learning - Nur Hamidatul Mauidloh; Syafi’ul Anam; Widyastuti Widyastuti (IJORER : International Journal of Recent Educational Research, 2024)
Objective: The rising popularity of gamification as an academic topic can be attributed to the growing affordability of Internet access through smartphones. One major challenge for gamification applications is maintaining student engagement and active participation. This research investigated whether students’ engagement and reading comprehension significantly correlated with using Quizlet for vocabulary learning at a public senior high school in Gresik. Method: This research used a correlational research design. The subject of this study consisted of 30 students who used Quizlet for vocabulary learning. The research instruments were a questionnaire and a data sheet on students’ reading scores collected from their teachers. The researcher used Descriptive and Pearson correlation through the SPSS Statistics 16.0 program to analyze the data. Results: This research revealed that students’ engagement was moderate while using Quizlet for vocabulary learning. Then, the correlation coefficient was 0.429*, and the significance 2-tailed value was 0.018. From the sig-value, there was a significant correlation between the two variables, and the correlation value showed that the correlation was positive in the moderate category. Students' engagement and reading comprehension while using Quizlet for vocabulary learning had a significant correlation with a moderate correlation, and this indicated that an increase followed most students' engagement increase in their reading comprehension. Novelty: This study significantly contributes to understanding how students' engagement influences their reading comprehension when using Quizlet for vocabulary learning. It also establishes a positive and statistically significant correlation with a coefficient of 0.429underscores that higher engagement levels correspond to improved reading comprehension outcomes.